Tacrolimus in Solution as an Option to Inflammatory Conditions of the Scalp - Camila Scharf; Gaetano Licata; Giulia Briatico; Sebastiano Pellerone; Giuseppe Argenziano; Caterina Mariarosaria Giorgio (Dermatology Practical & Conceptual, 2023)
Introduction: Several dermatological diseases lead to inflammatory conditions of the scalp. Most of these afflictions are recalcitrant and require long term maintenance treatment.